Oxidative RNA Damage in the Pathogenesis and Treatment of Type 2 Diabetes - Chen, Xiatian; Yu, Hua; Li, Zhe; Ye, Wei; Liu, Ziqian; Gao, Jinning; Wang, Yin; Li, Xin; Zhang, Lei; Alenina, Natalia; Bader, Michael; Ding, Hongyan; et al. (Frontiers in Physiology, 2022)
Excessive production of free radicals can induce cellular damage, which is associated with many diseases. RNA is more susceptible to oxidative damage than DNA due to its single-stranded structure, and lack of protective proteins. Yet, oxidative damage to RNAs received little attention. Accumulating evidence reveals that oxidized RNAs may be dysfunctional and play fundamental role in the occurrence and development of type 2 diabetes (T2D) and its complications. Oxidized guanine nucleoside, 8-oxo-7, 8-dihydroguanine (8-oxoGuo) is a biomarker of RNA oxidation that could be associated with prognosis in patients with T2D. Nowadays, some clinical trials used antioxidants for the treatment of T2D, though the pharmacological effects remained unclear. In this review, we overview the cellular handling mechanisms and the consequences of the oxidative RNA damage for the better understanding of pathogenesis of T2D and may provide new insights to better therapeutic strategy.